Passive smoking and type 2 diabetes among never‐smoking women: The Japan Public Health Center‐based Prospective Study - Oba, Shino (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: The aim of the current study was to prospectively evaluate the association between passive smoking from a spouse and the risk of diabetes among never‐smoking Japanese women. Passive smoking at a workplace (or public facilities) was assessed as a secondary measure. MATERIALS AND METHODS: In the Japan Public Health Center‐based Prospective Study (baseline 1990 or 1993), we followed 25,391 never‐smoking women aged 40–69 years and without diabetes. Passive smoking was defined as having a husband who was a self‐reported smoker, and the exposure at a workplace (or public facilities) was self‐reported by women. The development of diabetes was identified in questionnaires administered at the 5‐year and 10‐year surveys. A pooled logistic regression model was used to assess the association between passive smoking and the development of diabetes with adjustment for age and possible confounders. RESULTS: Compared with women whose husbands had never smoked, women whose husband smoked ≥40 cigarettes/day had significantly higher odds of developing diabetes in an age‐adjusted model, but the association was attenuated in a multivariable model (odds ratio 1.34, 95% confidence interval 0.96–1.87). There was a dose–response trend between the number of cigarettes smoked by a husband and the odds of developing diabetes (P = 0.02). Women reporting daily passive smoking at a workplace (or public facilities) had higher odds of developing diabetes than women reporting no such exposure (odds ratio 1.23, 95% confidence interval 0.995–1.53). CONCLUSIONS: Our results indicated a higher risk of diabetes among never‐smoking Japanese women with higher exposure to passive smoking from a spouse.